2024
DOI: 10.3390/md22010042
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-Assisted Coextraction of Phenolics and Polysaccharides from Padina gymnospora

Hoang Chinh Nguyen,
Kim Ngan Ngo,
Hoai Khang Tran
et al.

Abstract: Brown seaweed is a promising source of polysaccharides and phenolics with industrial utility. This work reports the development of a green enzyme-assisted extraction method for simultaneously extracting polysaccharides and phenolics from the brown seaweed Padina gymnospora. Different enzymes (Cellulast, Pectinex, and Alcalase), individually and in combination, were investigated, with Alcalase alone showing the highest efficiency for the simultaneous extraction of polysaccharides and phenolics. Yields from Alca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Therefore, it is important to investigate therapeutic approaches to treat this condition to prevent DEXA-induced muscle atrophy, introduce anti-muscle atrophy compounds to prevent important clinical implications, and investigate anti-muscle atrophy drugs or foods to treat these conditions effectively. Numerous studies have shown that enzyme-assisted extraction methods provide outstanding outcomes, including efficient extraction of bioactive compounds with greater extraction yields and protein content, which are highly recognized for superlative muscle growth [ 6 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important to investigate therapeutic approaches to treat this condition to prevent DEXA-induced muscle atrophy, introduce anti-muscle atrophy compounds to prevent important clinical implications, and investigate anti-muscle atrophy drugs or foods to treat these conditions effectively. Numerous studies have shown that enzyme-assisted extraction methods provide outstanding outcomes, including efficient extraction of bioactive compounds with greater extraction yields and protein content, which are highly recognized for superlative muscle growth [ 6 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%